Testing biowaste materials as peat replacement in organo-mineral fertilizers - Sitzmann, Tomas Javier; Sica, Pietro; Grignani, Carlo; Magid, Jakob (Frontiers in Sustainable Food Systems, 2024)
Organo-mineral fertilizers (OMFs) can have higher efficiency than mineral fertilizers. In Europe, peat is commonly used as an organic matrix in OMFs, as it is a highly stable organic material. However, peat extraction releases long-term stored organic C. Stabilized biowaste materials could replace peat in OMFs. Thus, this study aimed to understand how the variety of chemical properties in biowastes can influence OMF-soil interactions and nutrient availability to plants. Peat, green compost (GC), municipal solid waste compost (MSWC), and vermicompost (VC) were used as the organic matrix of OMFs with a C-N-P2O5 content of 7.5, 10, and 5%, respectively. OMFs were tested first in a ten-day plant-free incubation to measure Hedley P fractionation, nitrate, ammonium, total N in the soil, and CO2 and NH3 emissions. Further, a 30-day greenhouse trial measured maize yield and N and P use efficiencies. Controls included no fertilization (N0P0) and mineral N and P fertilization (MFNP). No differences were found in the incubation experiment for mineral N fractions in the soil. Fertilization significantly increased CO2 emissions, which were slightly higher in OMFs over MFNP, whereas OMFs significantly increased ammonia volatilization compared to MFNP. Available P had consistent results in the incubation and the greenhouse trials. Peat and MFNP had the highest waterand bicarbonate-P pools in the first experiment and higher yield and P use efficiency by maize. Therefore, OMFs from biowaste materials exhibited limited suitability for short growth cycles due to lower P use efficiency and higher ammonia volatilization. Treatment P(F) * ** ns ns *** ** *** * *